Paradoxical Implications of Article 7 Paragraph 1 of the Marriage Law in Indonesia - Andi Yaqub; Kamaruddin Kamaruddin; Iswandi Iswandi (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
This study aims to identify the paradoxical and anomalous factors in the marriage law in Indonesia, which are specifically described in Article 7 paragraph 1; which is then based on factual data regarding the marriage law and then strives to be able to produce more effective solutions in overcoming the implications of the paradox, especially in the marriage law. This study uses a normative legal research approach derived from the laws or regulations in the marriage that apply in Indonesia. This study has comprehensively described the fundamental factors of changes to the marriage law, which gave birth to conclusions regarding socially occurring facts, which are described in detail in the discussion and conclusion sections.